Advances of semiconductor mode-locked laser for optical frequency comb generation - Wei Wenqi; Chen Jiajian; Huang Jingzhi; Wang Zihao; Zhang Jianjun; Wang Ting (National Science Open)
Semiconductor mode-locked lasers (MLLs) can provide coherent optical frequency combs (OFCs) with high repetition rates and output power, which have been recognized as potential multi-wavelength sources used in optical communication field due to their compactness, high-efficiency, and low-cost properties. In this article, we have reviewed recent development of semiconductor MLL-based frequency comb generation. Different approaches of semiconductor MLLs for OFC generation are synoptically summarized based on various material platforms. The representative progress of III-V semiconductor MLLs on III-V platform and especially on Si substrates is both discussed for the applications in integrated silicon photonics.